Determinan Kejadian Needle Stick Injury (NSI) Pada Perawat di Unit Rawat Inap RSUD H. Abdul Manap Kota Jambi - Toybah, Ratu; Aswin, Budi; Kusmawan, David (Pusat riset dan Inovasi Nasional, 2025)
Based on observations, several cases of Needle Stick Injury (NSI) were found in nurses in the inpatient unit of RSUD H. Abdul Manap Jambi City during the vulnerable years 2022 to 2024. The risk of Needle Stick Injury (NSI) can cause infections such as HBV (Hepatitis B), HCV (Hepatitis C), and HIV (Human Immunodeficiency Virus). The purpose of this study was to determine the factors associated with the incidence of NSI in nurses in the inpatient unit of RSUD H. Abdul Manap Jambi City. This study is a quantitative study using an analytic survey with a cross sectional approach. The instruments used were structured questionnaires and observation sheets that were prepared based on literature review and had been tested for validity and reliability. This instrument selection was carried out to obtain data in accordance with the research objectives. The population in this study were 78 executive nurses in the inpatient unit with sampling using sampling techniques (total sampling). Data analysis used the chi-squre test to identify the determinants of the incidence of NSI. The results of this study showed the incidence of Needle Stick Injury (NSI) in nurses in the inpatient unit of RSUD H. Abdul Manap Jambi City who had experienced (43.6%) and who had not (56.4%). There is a relationship between K3 training and the incidence of Needle Stick Injury (NSI) (p = 0.000), work shifts with the incidence of NSI (p = 0.000), and there is no relationship between the use of PPE with the incidence of NSI (p = 0.278). It is concluded that there is a relationship between the incidence of Needle Stick Injury (NSI) in nurses at the inpatient unit of RSUD H. Abdul Manap Jambi City, namely K3 training and work shifts. While those that are not related, namely the use of PPE because it is not statistically significant.